Corporate Financial Management in The Digital Age: Challenges and Opportunities in Oversight and Transparency - Setiawan, Eko Agus; Hidayat, Riskin (JURNAL STUDI MANAJEMEN ORGANISASI, 2025)
This research aims to investigate the impact of digital technologies, such as blockchain and artificial intelligence (AI), in improving transparency, accountability, and efficiency in corporate financial management in the digital era. As organizations increasingly adopt these technologies, they present considerable opportunities and challenges. While digital technologies offer the potential to improve financial oversight, reduce fraud, and streamline decision-making processes, they also raise concerns regarding regulatory compliance, cybersecurity risks, and ethical considerations. The study identifies that rapid technological advancements have increased the demand for transparency and regulatory adaptation, with blockchain and AI playing a crucial role in real-time data validation and risk management. Technology integration often exceeds the ability of regulatory frameworks to adapt, creating gaps that can jeopardize governance and financial security. The research further explores the role of digital technology in enhancing corporate social responsibility (CSR) and stakeholder engagement, emphasizing the need for companies to balance technological innovation with social responsibility. Based on these findings, the study suggests that companies should update regulatory frameworks, improve cybersecurity measures, and ensure the ethical use of technology to maintain corporate integrity and public trust. The study also calls for further research to refine the method of evaluating the impact of digitalization on financial performance and corporate governance, especially in terms of ESG (Environmental, Social, and Governance) factors.